2017
DOI: 10.1063/1.4974993
|View full text |Cite
|
Sign up to set email alerts
|

All-dimensional H2–CO potential: Validation with fully quantum second virial coefficients

Abstract: We use a new high-accuracy all-dimensional potential to compute the cross second virial coefficient B12(T) between molecular hydrogen and carbon monoxide. The path-integral method is used to fully account for quantum effects. Values are calculated from 10 K to 2000 K and the uncertainty of the potential is propagated into uncertainties of B12. Our calculated B12(T) are in excellent agreement with most of the limited experimental data available, but cover a much wider range of temperatures and have lower uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…It has been demonstrated that the vibrationally averaged surfaces perform better than the rigid-monomer ones also in predictions of other physical properties, like rovibrational spectra 13 15 , 38 , 39 or virial coefficients. 40 , 41 A main drawback of such an approximation is that, in principle, to obtain the vibrationally averaged surface one has to know the corresponding full-dimensional one. To avoid construction of a full-dimensional surface and minimize the number of geometries for which ab initio calculations have to be performed, we use the method developed in ref ( 42 ).…”
Section: Theory With Resultsmentioning
confidence: 99%
“…It has been demonstrated that the vibrationally averaged surfaces perform better than the rigid-monomer ones also in predictions of other physical properties, like rovibrational spectra 13 15 , 38 , 39 or virial coefficients. 40 , 41 A main drawback of such an approximation is that, in principle, to obtain the vibrationally averaged surface one has to know the corresponding full-dimensional one. To avoid construction of a full-dimensional surface and minimize the number of geometries for which ab initio calculations have to be performed, we use the method developed in ref ( 42 ).…”
Section: Theory With Resultsmentioning
confidence: 99%
“…15 Full quantum treatment is needed to describe such motions, and the same is true for description of scattering of H 2 on CO. 16 The mixed second virial coefficient was calculated for this system using the path-integral Monte Carlo (PIMC) method. 17 The quantum approach has to be used for essentially all temperatures of interest; only above 1000 K can one rely on the classical values.…”
Section: Introductionmentioning
confidence: 99%
“…The current information on monomer-flexibility effects is limited. For the second virial coefficient of H 2 , Garberoglio et al 54 found that a rigid-monomer model with the bond length at its vibrationally averaged ground-state value gives results nearly identical to the fully flexiblemonomer calculation, and later effects of similar size (0.8% effect at 300 K and 0.09% at 1000 K) were found for H 2 -CO. 17 On the other hand, for H 2 O, it has been claimed that monomer flexibility has a large effect on B ( T ). Refson et al 55 computed this effect as 10% in the range 373–673 K, while Donchev et al 56 computed it as 20–40% for T ∊ 300 − 800 K, with 40% effect at 300 K. In contrast, recent calculations by Jankowski et al 21 gave much smaller monomer flexibility effects.…”
Section: Introductionmentioning
confidence: 99%
“…For the PES we used the recent high-accuracy 6D CO+H 2 potential reported by Faure et al [60,61]. This potential was chosen as it reproduces the proper physical inverse-power dependence with the intermolecular distance, R, at long range which is crucial for low energy collisions.…”
Section: Theoretical Approach a Scattering Calculationsmentioning
confidence: 99%